Crop protection: a multimedia tool for pest management - Bocar Bal, Amadou; Charles, Lucinda (Technical Centre for Agricultural and Rural Cooperation, 2005)
Amadou Bocar Bal and Lucinda Charles report that the Crop Protection Compendium is increasingly contributing to the identifi cation and management of crop diseases and pests in Africa